VIRTUAL LABORATORY TECHNOLOGIES AS A MEANS OF IMPROVING THE QUALITY OF UNIVERSITY STUDENTS' TRAINING (Web of Teachers: Inderscience Research, 2025)
The paper describes an approach to organizing laboratory workshops on electromagnetism, which consists in using the “Virtual Laboratory”. This approach made it possible to implement part of the educational process in a remote or front-line mode, reduce the costs of implementing laboratory workshops, reduce the risks of expensive equipment being damaged due to unskilled use, and implement new forms of work that are difficult to implement within a traditional laboratory (such as, for example, the introduction and troubleshooting). Practical classes in physics are an integral part of the discipline being studied. A clear and deep understanding of the basic laws of physics and its methods is impossible without working in a physics laboratory, as well as without performing home laboratory work. By conducting laboratory research, students not only confirm the known laws of physics, but also learn to work with physical instruments and master the skills of practical research. Interactive virtual laboratory and practical work is a learning environment that, using computer interactive visualization, allows schoolchildren to simulate a real experiment and conduct educational research. This is an educational environment aimed at ensuring the development of the student’s skills to independently generate new knowledge, formulate ideas, concepts, hypotheses about objects and phenomena, including previously unknown ones, recognize the deficits of their own knowledge and competencies, and plan their development.